2016
DOI: 10.1017/rdc.2016.92
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Stop Phenomenon Of Baobabs (Adansonia Spp.) Identified By Radiocarbon Dating

Abstract: The article reports the growth stop phenomenon, which was documented only for baobabs, i.e. for trees belonging to the Adansonia genus. The identification of growth stop was enabled by radiocarbon dating, which allows a complex investigation of samples collected from the trunk/stems of baobabs. In several cases, the outermost rings of baobabs, which were close to the bark, were found to be old, with ages of several hundreds of years, instead of being very young. Dating results of samples collected from six bao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…The research is based on our new approach which enables to investigate and date standing live specimens. This approach consists of AMS radiocarbon dating of tiny wood samples collected from different areas of such trees [3][4][5][6][7][8]. We extended our research by also investigating individuals which belong to other angiosperm species, including trees from Romania.…”
Section: Introductionmentioning
confidence: 99%
“…The research is based on our new approach which enables to investigate and date standing live specimens. This approach consists of AMS radiocarbon dating of tiny wood samples collected from different areas of such trees [3][4][5][6][7][8]. We extended our research by also investigating individuals which belong to other angiosperm species, including trees from Romania.…”
Section: Introductionmentioning
confidence: 99%
“…The research is based on our novel methodology, which is not limited to demised specimens, but also allows to investigate and date live individuals. This original approach is based on AMS (accelerator mass spectrometry) radiocarbon dating of tiny wood samples collected from inner cavities, deep incisions/entrances in the trunk, fractured stems and from the outer part/exterior of the trunk/stems of large baobabs [6][7][8][9][10][11][12][13]. We found that typically, all large African baobabs are multistemmed and preferentially exhibit ring-shaped structures.…”
Section: Introductionmentioning
confidence: 97%
“…We also identified the presence of false cavities, which are large natural empty spaces between several fused stems disposed in a closed ring-shaped structure, which have never been filled with wood [9][10][11][12][13]. The oldest dated A. digitata specimens were found to have ages greater than 2000 yr [14,15]. Dated growth rings of several African baobab specimens act as a proxy climate archive and have been used for past climate reconstruction in southern Africa [16,17].…”
Section: Introductionmentioning
confidence: 99%